(untitled) (Research, Society and Development, 2024)
Autologous dental transplantation is a surgical procedure that involves the transfer of a tooth, or part of a tooth, from one position to another in the same individual. This type of transplantation has a long history, dating back to ancient times, when doctors at the time made primitive attempts to replace teeth. Nowadays, autologous dental transplantation plays an important role in tooth replacement, especially in cases of dental trauma or agenesis of permanent teeth. The objective of this study is to analyze, through a narrative review, pertinent information about autologous dental transplantation, emphasizing the indications, techniques, and presenting the advantages of this transplantation in the face of early tooth loss. Therefore, analyses were carried out of scientific articles in the Scientific Electronic Library (Scielo) and PubMed platforms considered important for the chosen topic. Autologous dental transplantation is justified by the need to replace teeth in cases of traumatic loss or congenital absence. The importance of this technique lies in the fact that it offers a highly predictable and long-lasting treatment option for patients who require oral rehabilitation. Furthermore, autologous dental transplantation allows the preservation of bone tissue and the maintenance of aesthetics and masticatory function, contributing significantly to the quality of life of individuals undergoing the procedure. It is concluded that autologous dental transplantation is a viable and effective technique for tooth replacement in several cases, with the potential to offer long-lasting and satisfactory results.